Community Participation Approaches for Effective National COVID-19 Pandemic Preparedness and Response: An Experience From Oman - Al Siyabi, Huda; Al Mukhaini, Said; Kanaan, Mohsen; Al Hatmi, Sumaya; Al Anqoudi, Zahir; Al Kalbani, Ahmed; Al Bahri, Zakiya; Wannous, Chadia; Al Awaidy, Salah T. (Frontiers in Public Health, 2021)
Oman, like other countries in the world, was affected by the COVID-19 pandemic. Since the WHO's declaration of the pandemic, the Ministry of Health of Oman has initiated its preparedness and response to the pandemic, with community participation as one of the key components of the national preparedness and response plan. This paper is a descriptive study aims at describing the three community approaches that exist in Oman and reviewing their role in preparedness and response strategies to COVID-19 pandemic and discuss the lessons learned. Community participation approaches in Oman were translated into action during the pandemic through empowering community members, mobilizing resources, and strengthening the ownership among the local community to ensure effective advocacy, proper networking, and dissemination of information and, subsequently, actions at the level of the community. The first community participation approach is community organizations within the healthy cities and villages initiative, which facilitated networking and acted as a platform for community engagement, reviewing the health information and updating them accordingly to meet evloving demands. The second approach is Willayat (District) health committees, with their unique multi-sectoral structure, that enhanced collaboration at the state level with different community leaders and groups to develop pandemic action plans, which were implemented using available local resources. The third approach is community volunteers that remain the key information providers, particularly when physical access becomes limited due to physical distancing measures. Based on this review, we advocate to further strengthen these approaches and recommends that they are implemented for the protection and promotion of health and well-being, including for health emergencies.